Siri’ na Pacce cultural transformation and blue economy for social and cultural resilience towards the golden generation of 2045 - Pratama, Nanda Rezky; Iswar; Hasan, Muhammad (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: This study develops a conceptual model that integrates maritime cultural revitalization and indigenous ethics with digital transformation and sustainable economic strategies to address the socio-ecological threats faced by the Patorani fishing community. By bridging traditional values and modern innovations, this study provides a strategic framework for coastal resilience that is aligned with Indonesia's Golden Generation 2045 vision. Methods: This article employs a structured, integrative literature review that synthesizes existing scholarship on maritime heritage, community ethics, digital innovation, blue economy frameworks, and coastal sustainability. Relevant theoretical perspectives were identified and analyzed to establish linkages between cultural systems, technological adaptation, and socioeconomic development. Unlike empirical studies, this conceptual work aims to consolidate theoretical components, identify gaps in current literature, and propose an interdisciplinary framework for coastal resilience. Findings: The review reveals that maritime traditions are experiencing significant erosion due to environmental pressures such as declining fish stocks, pollution, and coastal degradation, as well as socio-cultural challenges including shifting generational preferences and the commodification of cultural symbols. Despite these pressures, the indigenous ethical framework of Siri’ na Pacce remains a strong yet underutilized form of moral capital that can guide ethical innovation, social cohesion, and community-based governance. Digital technologies such as e-commerce, digital storytelling, virtual cultural festivals, and online knowledge platforms offer new opportunities to strengthen youth engagement, expand economic access, and revitalize cultural identity. The integration of technologically driven practices with cultural ethics and blue economy principles shows strong potential to enhance livelihood sustainability and ecosystem stewardship. Conclusion: The study concludes that sustainable coastal development must be culturally grounded, technologically adaptive, and environmentally responsible to remain relevant in the contemporary era. Novelty/Originality of this article: The primary novelty of this research lies in its formulation of the Patorani 5.0 model, which for the first time unites cultural revitalization, ethical values, digital transformation, and blue economy strategies into an integrated conceptual framework, addressing scholarly gaps that previously treated these domains in isolation.